PENGARUH PEMBERIAN JUS JAMBU BIJI MERAH DAN JUS JERUK TERHADAP PENINGKATAN KADAR HEMOGLOBIN IBU HAMIL - Dian Zuiatna; Nurrahmaton Nurrahmaton; Nabilla Arraudhah (LPPM Universitas Abdurrab, 2025)
Anemia in pregnant women is a decrease in hemoglobin levels below 11 gr/dl, first and third trimesters or levels < 10.5 gr/dl in the second trimester. Anemia in pregnant women is closely related to maternal and infant morbidity and mortality, including the risk of miscarriage, prematurity, low birth weight babies. In pregnant women, anemia increases the frequency of complications in pregnancy and childbirth. The risk of maternal death, low birth weight, prematurity and perinatal death rates increases. The aim of this study was to determine the frequency of giving red guava juice and orange juice to increase hemoglobin levels in pregnant women with anemia at PMB Juliani Bandar Khalipah. This research was conducted in June – October 2023. The research design used a Quasy Experiment with one group pretest and posttest. The population in this study was 10 pregnant women with anemia, the sampling technique used purposive sampling, with sampling using inclusion and exclusion criteria, a sample of 6 people was obtained. Data analysis was carried out using the Shapiro-Wilk normality test and then the Wilcoxon test. The results of the study showed that there was an effect of giving red guava juice and orange juice on increasing hemoglobin levels in anemic pregnant women, with a sig (2-tailed) value of 0.034 <0.05. The conclusion in this study was that there was an effect of giving red guava juice and orange juice on increasing hemoglobin levels in pregnant women with anemia. It is hoped that pregnant women can consume red guava juice and orange juice to prevent anemia during pregnancy.